2022
DOI: 10.3233/cbm-210159
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics-guided analysis uncovers TIGIT as an epigenetically regulated immunomodulator affecting immunotherapeutic sensitivity of gastric cancer

Abstract: BACKGROUND: Immunomodulatory genes play significant roles in the regulation of immunological properties of gastric cancer, but the effect of epigenetic regulation of these genes on the immune properties is unknown. METHOD: I analyzed the methylation-expression correlation among all immunomodulators and compared with the non-immunomodulators. The association between epigenetically regulated immunomodulators (ERI) and tumor microenvironment is evaluated. A key immunomodulator TIGIT is further selected to investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…On the other hand, TIGIT may be a potential target for designing epigenetic drugs. 433 Since TIGIT and PD-1 can be highly co-expressed in CD8 + T cells, 431 TIGIT is expected to be a target for potentiating the benefits of anti-PD-1 therapy.…”
Section: Signaling Pathways In Gastric Cancer and Therapeutic Implica...mentioning
confidence: 99%
“…On the other hand, TIGIT may be a potential target for designing epigenetic drugs. 433 Since TIGIT and PD-1 can be highly co-expressed in CD8 + T cells, 431 TIGIT is expected to be a target for potentiating the benefits of anti-PD-1 therapy.…”
Section: Signaling Pathways In Gastric Cancer and Therapeutic Implica...mentioning
confidence: 99%
“…The role of epigenetics in TIGIT expression and immunotherapeutic sensitivity was also uncovered in gastric cancer. Increased TIGIT expression in gastric cancer appears to be a favorable event ( 152 ). TIGIT expression correlates with an active immune landscape, survival and immunotherapeutic sensitivity, and favorable prognosis, according to a bioinformatics-guided analysis.…”
Section: Tigit In Cancer Progressionmentioning
confidence: 99%
“…TIGIT expression correlates with an active immune landscape, survival and immunotherapeutic sensitivity, and favorable prognosis, according to a bioinformatics-guided analysis. Patients with high TIGIT expression respond better to immunotherapy than those with low TIGIT expression ( 152 ).…”
Section: Tigit In Cancer Progressionmentioning
confidence: 99%
“…Tyrosine-based inhibition motif domain (TIGIT) is an important immune checkpoint for T/NK cells 25 . It has been found that TIGIT can be detected at breast cancer 26 , renal cell carcinoma 27 , lung adenocarcinoma 28 , hepatocellular carcinoma 29 , gastric cancer 30 , acute myeloid leukemia 31 , melanoma 32 and promote tumor onset, progression and prognosis 33 , 34 . TIGIT is expressed on human tumor-infiltrating CD8+ T cells, NK cells, Th and Treg cells in melanoma 35 .…”
Section: Discussionmentioning
confidence: 99%